University proceedings. Volga region. Medical sciences - V.V. Maslyakov; A.G. Proshin; T.A. Proshin; F.A. Sanbaev; D.S. Khlamov (Известия высших учебных заведений. Поволжский регион: Медицинские науки)
Background. To conduct a study of the nature of injuries to the civilian population as a result of gunshot wounds and the nature of assistance for such injuries at the prehospital stage. Materials and methods. The study is retrospective, in order to achieve this goal, an analysis of the results of treatment of 46 wounded civilians who were injured in the facial area in a local military conflict was carried out. Of the total number of women surveyed, there were 15 (32.6%), and men – 31 (67.3%) people. The average age was 38 ± 4 years. Results and conclusion. It was found that most of the victims of gunshot wounds received multiple wounds, which led to injuries of moderate severity – 45,6%. Facial injuries led to capillary bleeding, which was noted in 82.6% of the victims. At the same time, selfand mutual assistance prevailed as first aid for such wounded people at the scene – 50% of observations. It should be noted that such assistance was performed in full and correctly in 80.4% of the observations, in the remaining 13.0% of cases errors were noted related to incorrect dressing and failure to perform temporary hemostasis. Moreover, all errors were recorded during the provision of first aid by random witnesses who do not have the skills to provide such assistance. As a result of the analysis, it was found that the correctness and timeliness of first aid is of great importance in the development of complications in the wounded in the immediate postoperative period.